Mammary epithelial cells isolated from milk are a valuable, non-invasive source of mammary transcripts - Boutinaud, Marion; Herve, Lucile; Lollivier, Vanessa (Frontiers in Genetics, 2015)
Milk is produced in the udder by mammary epithelial cells (MEC). Milk contains MEC, which are gradually exfoliated from the epithelium during lactation. Isolation of MEC from milk using immunomagnetic separation may be a useful non-invasive method to investigate transcriptional regulations in ruminants’ udder. This review aims to describe the process of isolating MEC from milk, to provide an overview on the studies that use this method to analyze gene expression by qRT PCR and to evaluate the validity of this method by analysing and comparing the results between studies. In several goat and cow studies, consistent reductions in alpha-lactalbumin mRNA levels during once-daily milking (ODM) and in SLC2A1 mRNA level during feed restriction are observed. The effect of ODM on alpha-lactalbumin mRNA level was similarly observed in milk isolated MEC and mammary biopsy. Moreover, we and others showed decreasing alpha-lactalbumin and increasing BAX mRNA levels with advanced stages of lactation in dairy cows and buffalo. The relevance of using the milk-isolated MEC method to analyze mammary gene expression is proven, as the transcript variations were also consistent with milk yield and composition variations under the effect of different factors such as prolactin inhibition or photoperiod. . However, the RNA from milk-isolated MEC is particularly sensitive to degradation. This could explain the differences obtained between milk-isolated MEC and mammary biopsy in two studies where gene expression was compared using qRT-PCR or RNA Sequencing analyses. As a conclusion, when the RNA quality is conserved, MEC isolated from milk are a valuable, non-invasive source of mammary mRNA to study various factors that impact milk yield and composition (ODM, feeding level, endocrine status, photoperiod modulation and stage of lactation).